Hybrid access control algorithm based on relay node assistant in Femtocell network - Cheng-yi LIU; Geng CHEN; Song XING; Lian-feng SHEN (Tongxin xuebao)
A Femtocell hybrid access control algorithm assisted with relay note was proposed to supply higher performance for the Femtocell neighboring users (NUE) in heterogeneous network.Deploying relay outside the Femtocell networks was used and amplify-and-forward (AF) relaying protocol or direct link protocol was alternated to use for the data transmission of Femtocell NUE.An optimization problem was formulated with the constraints of the required transmission rates thresholds of Femtocell registered users (FUE),the thresholds of the cross-tier interferences to the macrocell users (MUE),and total transmit powers of the Femtocell base station (FBS).By using the dual decomposition method,a Femtocell hybrid access control algorithm was given based on the combination of the direct mode and relay mode.Simulation results have shown that the scheme can not only protect the QoS required by the FUE,but also decrease the cross-tier interferences suffered by the MUE.It also illustrates the better performance of the NUE through the dynamic and flexible access mechanism.Furthermore,based on the last simulation the relay link would help the NUE obtain about 25% more performance than the traditional direct link in some regions.